2004
DOI: 10.1111/j.1460-2695.2004.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical analysis of crack tip stress fields: a comparative study

Abstract: A B S T R A C T Four optical techniques for evaluating stress intensity factors in opaque specimens are described in outline, and compared for both an artificial crack and a fatigue crack. The results are compared to a standard solution for the geometry considered. All the techniques gave acceptable results over a range of stress levels and crack lengths. The methods of caustics and strain gauges were less good, whilst photoelasticity gave consistent results over a wide range of stress levels. Comments on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The caustics have been successfully applied to determine the stress intensity factor of cracks under mode I loading as well as the triaxial state of stresses near the crack tip. That method has been also used to study the dynamic fracture behaviours of homogenous and isotropic material …”
Section: Introductionmentioning
confidence: 99%
“…The caustics have been successfully applied to determine the stress intensity factor of cracks under mode I loading as well as the triaxial state of stresses near the crack tip. That method has been also used to study the dynamic fracture behaviours of homogenous and isotropic material …”
Section: Introductionmentioning
confidence: 99%
“…Photoelasticity is one of the most reliable and widely accepted techniques for fracture studies, and it has long been used for the investigation of stress field around a propagating crack tip [19,20]. However, it is found that isochromatic fringes cannot be observed for a thin glass specimen because glass exhibits low birefringence.…”
Section: Introductionmentioning
confidence: 99%
“…There are no modern experimental methods that allow directly determining the stress distribution as well as the SIFs and T ‐stresses along the curved crack front from the experimental data in certain areas of the object. Thus, the second approach can be connected with experimental methods for determination of the SIF and the T ‐stress at narrow range of the problem, namely experimental measurement of the SIF and the T xx ‐stress in the vicinity of the through‐thickness crack.…”
Section: Introductionmentioning
confidence: 99%